AIRLINE RESPONSIBILITY FOR PASSENGER DEPARTURE CANCELLATIONS DUE TO NOT COMPLETING HEALTH REQUIREMENTS ( RAPID TEST )(Research Study at Kuala Namu Airport) - Budiman (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Factors that cause airlines to cancel flights include commercial, technical, operational, weather, and airport factors. Airlines are responsible for canceling departures due to health care requirements (accelerated testing): if a passenger tests positive for antigen, they must undergo a PCR test; if negative, they can continue, and the price of the ticket is returned to fly back at least 3 days later. If the passenger gets a PCR test, they must quarantine for 14 days, rescheduling the ticket according to the passenger's status after quarantine. Or the entire ticket will be refunded. There are no specific provisions for consumer legal protection for departure cancellations due to failure to complete health care (accelerated testing), but compliance is not limited to Law Number 1 of 2009 concerning Aviation is not achieved. However, passengers as consumers have legal protection under the Consumer Protection Law relating to passenger rights as consumers of air transportation services, and the Civil Code relating to the status of passengers as parties to a transportation contract with airlines.